2014
DOI: 10.1371/journal.pbio.1001933
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Capping Complex Assembles on Adapter Protein Nck1 Bound to the Proline-Rich C-Terminus of Mammalian Capping Enzyme

Abstract: mRNA capping and decapping requires a cytoplasmic complex to maintain and/or restore the 5′ cap on a subset of the mammalian transcriptome; Nck1, an SH2/SH3 adapter, creates a scaffold upon which the cytoplasmic capping complex forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 36 publications
3
59
0
4
Order By: Relevance
“…[10] These interactions require N7 methylation, and unmodified caps have been show to become remethylated in the cytoplasm. [11] We measured the K d values of recombinantly produced eIF4E and the inactive variant DcpS (H277N) for the native and modified cap and found that these proteins do not bind to N7-BP-modified-GpppA (10d), whereas m 7 GpppA is bound, showing a K d value in the sub-micromolar range,w hich is in line with reported values (Figures S40, S41, Table S1). [10d,21] After irradiation and enzymatic remethylation to mimic cellular remethylation, binding to both proteins was fully restored (Figure 4C,D).…”
Section: Angewandte Chemiesupporting
confidence: 81%
See 1 more Smart Citation
“…[10] These interactions require N7 methylation, and unmodified caps have been show to become remethylated in the cytoplasm. [11] We measured the K d values of recombinantly produced eIF4E and the inactive variant DcpS (H277N) for the native and modified cap and found that these proteins do not bind to N7-BP-modified-GpppA (10d), whereas m 7 GpppA is bound, showing a K d value in the sub-micromolar range,w hich is in line with reported values (Figures S40, S41, Table S1). [10d,21] After irradiation and enzymatic remethylation to mimic cellular remethylation, binding to both proteins was fully restored (Figure 4C,D).…”
Section: Angewandte Chemiesupporting
confidence: 81%
“…[10] Due to its importance in biology,wechose the N7 position of guanosine for modification with functional groups with the goal of removing them upon irradiation with light and recover the free guanosine.Inthe 5' cap of mRNAs, the Gb ecomes remethylated in cells. [11] To generate photocaged guanosines in different contexts,t hat is,f rom single nucleosides to long mRNAs,wedevised both achemical and an enzymatic preparative route (Scheme 1). PC groups for nucleosides that do not substitute ah ydrogen atom but instead introduce apositive charge have not been reported to date to the best of our knowledge.…”
mentioning
confidence: 99%
“…Although Nck1 and Nck2 share common functions and interacting proteins (38), studies have reported specific functions and exclusive binding partners for Nck proteins (39)(40)(41). In agreement, we showed that Nck1-deficient mice display normal glucose homeostasis (15), and in the current study, we report that Nck2-deficient mice spontaneously develop progressive increased adiposity concomitant with impaired glucose homeostasis, insulin resistance, and hepatic steatosis.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to mammals, downstream CAGE tags are absent from the Drosophila transcriptome [15]. This raised the possibility that Drosophila lacks one or more of the biochemical mechanisms needed for downstream capping, and it was this idea that led us to perform the phylogenetic analysis in [6] that identified the basis for this. That analysis identified a proline rich sequence at the C-terminus of mammalian capping enzyme whose absence from Drosophila capping enzyme precludes it is binding to Nck1, and therefore, its ability to participate in cytoplasmic capping.…”
Section: Relationship Of Cage Tags To Recapping Sitesmentioning
confidence: 99%